Case study on perspicacity of collaborative learning experiences - Abdullah, Fadzidah; Abdul Majid, Noor Hanita; Numen, Ibrahim; Azmin, Aida Kesuma; Abdul Rahim, Zaiton; Denan, Zuraini; Sisman, Muhammet Emin (IOP Publishing, 2018)
In the attempt to relate to the architectural practice, architectural education today has augmented the development of collaborative learning environment in the campus scenario. Presently, collaborative work among students from the same program and university is considered common. Hence, attempts of collaboration are extended into having learning and teaching collaboration by means of inter-universities. The School of Architecture, at the International Islamic University Malaysia (IIUM), has explored into having collaboration across the continent with Fatih Sultan Mehmet Waqf University (FSMWU), among faculty members and students of the two (2) universities This paper explicates the empirical study on students’ perspicacity of their collaborative learning experiences; in term of effectiveness, generative behavior, and teamwork. A survey with three (3) open-ended questions are distributed to students to express their opinions on learning collaboration that they have had during the execution of the Joint Summer School Program (JSSP). Feedback on their perspicacity is obtained and organized into numerical and understandable data display, using qualitative data processing software. Albeit the relevancy of collaborative learning, students gave both positive and negative feedback on their experiences. Suggestions are given to enhance the quality of collaborative learning experience for future development.